Teachers’ literacy-related knowledge and self-perceptions in relation to preparation and experience - Spear-Swerling, Louise; Brucker, Pamela Owen; Alfano, Michael P (Annals of Dyslexia, 2005)
After rating their own literacy-related knowledge in three areas (knowledge about reading/reading development, phonemic awareness/phonics, and morpheme awareness/structural analysis), graduate teacher-education students completed five tasks intended to measure their actual disciplinary knowledge in these areas. Teachers with high levels of prior background (i.e., course preparation and experience) rated themselves as significantly more knowledgeable than did low-background teachers in all areas; high-background participants also significantly outperformed low-background participants on all tasks. However, even high-background teachers scored well below ceiling on the tasks. Regression analyses indicated that teachers' self-perceptions and knowledge were positively influenced by both level of preparation and teaching experience, although the influences on teachers' knowledge differed by task. Teachers had some accurate perceptions of their own knowledge, especially in the area of phonics. Results suggest that differentiating levels of preparation may be useful in studying teacher knowledge, and also support the notion of a substantial gap between research on reading and teacher preparation in reading.
57 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-385-164-145-266 tex.type: [object Object]
Keywords: *Faculty; *Phonetics; *Professional Competence; *Reading; *Self Concept; Adult; Certification; Child; Credentialing; Education; Graduate; Education; Special; Educational Measurement; Faculty; Female; Humans; Literacy; Male; Phonetics; Professional Competence; Professional development; Reading; Self Concept; Semantics; Teacher education; Teacher knowledge; Teacher perceptions; Teacher preparation; United States; Vocabulary; academic achievement; accreditation; adult; article; certification; child; dept.sed; education; female; human; linguistics; male; phonetics; professional competence; reading; self concept; semantics; university